Strengthening National Resilience Through Family Resilience Education (Case Study of Kohati Bandung Women's School Program) - Pratiwi, Elda Dwi (Jurnal Civicus, 2024)
The vulnerability of family resilience can affect the vulnerability of national security, because national resilience will materialize if it is supported by environmental resilience, family resilience and individual resilience. Ideally, the family is the first place of learning for individuals, especially in terms of morals and character. However, families often experience vulnerabilities that lead to domestic violence, divorce, juvenile delinquency, and even the emergence of terrorism which allegedly originated from the family's passive role as a child's character builder. The purpose of this study was to examine family resilience education in the Kohati women's school program, the Bandung branch, as an effort to strengthen national resilience. The research took place at the Graha HMI Bandung branch as the place for the program. This research uses a qualitative approach with a case study method. Data were collected using interviews, observation, documentation, and literature studies. The data analysis consists of three stages: data reduction, data presentation, and drawing conclusions. The women's school program can be seen as the development of civic education in society in realizing the importance of building national resilience through building family resilience. Aspects developed in building family resilience as the foundation of national resilience include: family integrity and legality, family physical resilience, family economic resilience, family psychological resilience and family socio-cultural resilience. However, this girls' school program does not yet have an integrated curriculum as non-formal education in the community. There are obstacles in program planning, implementation and evaluation. It is interesting to study further about the development of learning models in civic education in community education programs as an effort to build citizen competence.